1999
DOI: 10.1161/01.cir.99.23.3017
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Anatomy of the Inferior Right Atrial Isthmus in Patients With and Without History of Common Atrial Flutter

Abstract: The inferior isthmus and right atrium in patients with common atrial flutter were significantly larger than those in a control population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
106
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 18 publications
8
106
1
Order By: Relevance
“…An isthmogram was performed by positioning a 5F pigtail catheter in the IVC just at the level of the splenic and hepatic veins. 9,10 Contrast solution was injected during 3 to 5 seconds for a total of 50 cm 3 in each patient. The angiograms were digitally acquired, thus allowing replay and storage of right anterior oblique (RAO) frames as reference during the subsequent ablation.…”
Section: Right Atrial Angiographymentioning
confidence: 99%
See 2 more Smart Citations
“…An isthmogram was performed by positioning a 5F pigtail catheter in the IVC just at the level of the splenic and hepatic veins. 9,10 Contrast solution was injected during 3 to 5 seconds for a total of 50 cm 3 in each patient. The angiograms were digitally acquired, thus allowing replay and storage of right anterior oblique (RAO) frames as reference during the subsequent ablation.…”
Section: Right Atrial Angiographymentioning
confidence: 99%
“…14,23 Impact of Right Atrial Length and Anatomy for AFL RFA Previous anatomic and angiographic reports studying human hearts have pointed to the anatomic variability of the isthmus, reporting an average width of 27Ϯ3.3 to 37Ϯ8 mm and different morphologies. 9,10,24 In a landmark study, the authors revealed a highly variable isthmus anatomy and its impact to adjust the ablation tactic. 10 The presence of a eustachian valve or concave isthmus was associated with statistically more RF applications, and the same trend was seen for patients with deep pouches.…”
Section: Comparison Between 8-mm-tip and Cooled-tip Cathetersmentioning
confidence: 99%
See 1 more Smart Citation
“…The width of the isthmus in the RAO view was measured between the IVC and the lower hinge point of the tricuspid valve (points A and B in Figure 1A). The isthmus often could be divided into a recess (inferoposterior to the CS ostium) and a flat vestibule (between this recess and the TA) 11 : The width of each was measured. The perpendicular distance between the line connecting A and B and the deepest point of the isthmus was quantified.…”
Section: Ra Angiographymentioning
confidence: 99%
“…Right atrial angiography is a widely available and inexpensive alternative. 11 We postulated that visualizing the anatomic conformation of the isthmus could rationalize the ablation approach.…”
mentioning
confidence: 99%